Abkhaz and Abazin Communities in Cyberspace - Tamara G. Ayba (Changing Societies & Personalities)
The article explores the strategies implemented by two related Indigenous peoples, Abkhaz and Abazins (Abaza), aimed at preserving ethnic culture in the context of virtual space. For Abkhaz and Abazins living abroad, it is essential to demonstrate their unity with their historical homeland, their belonging and inseparability from their traditions. Therefore, they take photos and videos of celebrations of traditional holidays, post them on social networking sites, thus indicating that they are an integral part of their people, regardless of the fact that they live outside. At the same time, the Abazins who are living in Russia, also use virtual communication for the popularization and revival of traditional culture. A content analysis was performed to study ethno-characteristic, linguistic, local, extra-territorial communities in popular social networks such as VK, Odnoklassniki, Telegram, Instagram, Facebook. As a result, the main trends that Abkhaz and Abazins use in cyberspace to keep their Indigenous culture alive were traced. In addition, the confrontation between classical Islam and traditional beliefs, which are an integral part of the ethnic culture of these two peoples, was revealed.